A comparative study on intraoperative mitomycin-c augmented external dacryocystorhinostomy with conventional dacryocystorhinostomy - Puzari, Bharoti Sarmah; H. N., Pramod Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Dacryocystorhinostomy (DCR) is a commonly done surgery performed for management of epiphora due to nasolacrimal duct obstruction. Goal of the procedure is to bypass the obstructed nasolacrimal duct allowing tear drainage into the nasal cavity directly from lacrimal sac by creating an anastomosis between the lacrimal sac and the nasal mucosa via a bony ostium. Common cause of DCR failure are attributed as an end effect of fibrous tissue growth, scarring and granulation tissue formation which obstructs the new drainage channel. Mitomycin c is an antiproliferative agent and may enhance the result of DCR by inhibiting fibrous tissue proliferation. Here we aim to evaluate the results of intraoperative mitomycin C application in dacryocystorhinostomy surgery compared with the result of conventional DCR. Methods: A prospective randomized comparative study of one year duration was done in the Department of Ophthalmology, Assam Medical College and Hospital, Dibrugarh, Assam, India. A total of 60 patients of acquired nasolacrimal duct obstruction were enrolled and divided randomly into two groups, 30 nos of patients in each group. One group had undergone conventional external DCR operation and other group was treated with DCR surgery with intraoperative mitomycin C application at the anastomotic flap and osteotomy site. Patients were reviewed after 1week, 1month, 3month and 6months postoperatively. The results of DCR surgeries were evaluated by observation of different parameters such as height of tear meniscus and patency of the nasolacrimal passage. Results: In our study we have observed that majority of cases were in 21-30 years age group with female preponderance (male vs female; 35% vs 75%). Chronic dacryocystitis was seen in majority of cases (70%) followed by mucocele (26.67%) and lacrimal fistula (3.33%). Major difficulties encountered during surgery and postoperatively were almost identical in both the groups. There was no case of abnormal mucosal bleeding, mucosal necrosis, delayed wound healing in patients which underwent DCR with mitomycin C use. Post-operative care and follow up were done identically in both the groups. It was seen that a total success rate of 80% was achieved in conventional group where as 96.67% success was achieved in MMC group at the end of 6 months. In case of scar prone conditions like lacrimal fistula mitomycin C use has shown to be efficacious in maintaining patency of the system after surgery. Conclusions: Distinctly higher success rate have been achieved in patients undergoing DCR with intra-operative MMC as compared to patients undergoing conventional DCR. Use of intraoperative mitomycin C can be considered safe and simple but very effective modification of conventional external DCR.